Project-Based Assessment Blended Learning To Improve Students' Psychomotor Competence - Rahayu, Wening Patmi; Zutiasari, Ika; Ningsih, Giarti (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2022)
This research and development aim to produce an appropriate blended learning-based assessment project that can improve student competence. Project assignment by utilizing various contemporary applications such as Tik Tok, Instagram, and Youtube as a medium for product promotion. The data were researched and developed using Research and Development methods, the research model used was adopted from Borg & Gall. The feasibility of the development product in the form of an instrument was validated by a validator of assessment experts, validators of material experts. Student competence is measured by cognitive and psychomotor aspects. Data analysis by percentage and paired sample T-test analysis. The results of expert validation were declared